IbM POSDAYA KUSUMA JAYA KELURAHAN MUKTIHARJO KIDUL KECAMATAN PEDURUNGAN KOTA SEMARANG - Eko Retno Mulyaningrum; Suwarno Widodo; Muniroh Munawar (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2014)
AbstractEach Posdaya (Pos Pemberdayaan Keluarga/Family Empowerment Post) is expected to have four important pillars: education, health, entrepreneurship, and the environment. Posdaya Kusuma Jaya which is the best Posdaya in Semarang is located in the South Muktiharjo still not optimal in developing Posdaya in the environmental field. So there needs to maximize the field of innovation through the creation of an aquaponics. Aquaponics is an integrated crop cultivation techniques with fish ponds, the use of continuous water from fish to plant maintenance and vice versa from the plant to the fish pond. The basis of the system of this technology is the optimum water supply for each commodity by using re-circulating system. In conclusion through IbM Posdaya Kusuma Jaya Muktiharjo Kidul Pedurungan Semarang community can optimize one Posdaya field is the field of the environment. Besides, this IbM hopefully can increase knowledge and skills of the people in the manufacture of aquaponics.Keywords: Posdaya, Aquaponics, Environment